1994
DOI: 10.1007/bf00006801
|View full text |Cite
|
Sign up to set email alerts
|

The Ethiopian Rift Valley lakes: chemical characteristics of a salinity-alkalinity series

Abstract: The study on 10 lakes within the Ethiopian Rift Valley during March-May 1991 covered a range of conductivity (K 25 ) between 286 and 49100 /S cm '. HCO 3 -CO32-and Na + were the dominant ions in all the lakes. Concentrations of K', Cl-and SO4-increased with increasing salinity and alkalinity, whereas Ca 2+ and Mg 2 + decreased. Comparison of these data with previous records showed that a ten-fold dilution of total ionic concentration occurred over 30 years in Lake Metahara and about three-fold increase occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
100
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 22 publications
16
100
4
Order By: Relevance
“…For the majority of the samples collected and analysed by the author the analytical error is less than 5%. Certainly there is limitation in data quality from literature works (UNDP, 1973; Elizabeth Kebede et al, 1996); none of the data sources indicate the accuracy and analytical errors. However, for such a regional work the analytical procedures and results are of acceptable quality.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the majority of the samples collected and analysed by the author the analytical error is less than 5%. Certainly there is limitation in data quality from literature works (UNDP, 1973; Elizabeth Kebede et al, 1996); none of the data sources indicate the accuracy and analytical errors. However, for such a regional work the analytical procedures and results are of acceptable quality.…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…The exception to this is the expanding L ake Beseka which underwent substantial dilution due to substantial groundwater flow from the surrounding over-irrigated mechanized farms (Elizabeth Kebede et al, 1996;Zenaw Tessema, 1996;WWDSE, 2000; due to the introduction of water from surrounding irrigation fields, which uses the Awash River. The most exceptional lake in the Afar is Lake Afdera, which is located at about 80 meters below sea level.…”
Section: Physiography and Hydrochemistrymentioning
confidence: 99%
“…Compilation of the sparse chemical data available since 1926 (Kebede et al, 1996) and chemical analysis since 1995 (Ayenew, 1998) has revealed a considerable increase in the total dissolved solids. Between 1926 and 1998, the salinity fluctuated more than 2.6 times (from 8.1 to 26 mg F 1 ), the alkalinity changed from 80 to 326 mg F 1 , and pH varied between 9.5 and 10.1.…”
Section: Resultsmentioning
confidence: 99%
“…In the last few decades, the ever-growing utilization of water resources in the rift and adjacent highlands has induced salinization of irrigation fields and lake level changes (Hailu et al, 1996;Ayenew, 1998). The chemistry and ecological setting of some of the lakes has changed (UN, 1973;Makin et al, 1976;Kebede et al, 1996). The main controlling factors are not well understood, particularly the relative importance of natural and manmade factors.…”
Section: Open For Discussion Until 1 December 2002mentioning
confidence: 99%
“…Barker et al, , pH=8) to hyper-alkaline waters in the lowest lake Shala (>20,000 57 µS.cm -1 , pH=10) (Kebede et al, 1994, Legesse and Ayenew, 2006). In the middle of the system, lake…”
mentioning
confidence: 99%